Utilização de diferentes carvões ativados no preparo de compósitos com óxido de ferro para o uso na remoção de corante têxtil - Kafer, Maiara (2021)
Two different activated charcoal types, from discarded domestic water filters (CAD) and commercial bone char (BC) were used in the preparation of composites with iron oxide aiming their use in the removal of textile dye in aqueous solution. The composites were prepared by the impregnation of activated charcoal with Fe (NO3)3.9H2O solution and subsequent thermal decomposition, with the generation of iron oxide. The activated carbon (CAD and BC) and the two composites (CAD/Fe and BC/Fe) were characterized by SEM, N2 physisorption, FTIR, XRD, determination of iodine number, point of zero charge (pHPZC), leaching test of Fe and H2O2 decomposition. The results indicated the presence of hematite in the composites. The presence of iron oxide contributed to reduce the surface area and pore volume of the composites in comparison to the original activated carbon. The pHPZC was 6.36, 5.97, 7.78 and 8.52 for the CAD, CAD/Fe, BC and BC/Fe samples, respectively. The adsorption tests of textile dye RB5 revealed BC and BC/Fe samples able to adsorb greater amount of dye in comparison to CAD and CAD/Fe samples, due to their predominantly mesoporous structure. In RB5 removal tests with the presence of H2O2 a combined process of adsorption and oxidation was evidenced in CAD sample and CAD/Fe composite, enhancing dye removal. However, this combined process was not observed in the BC/Fe composite, mainly due to its high pHPZC. Therefore, in addition to the pore characteristics, chemical composition of activated charcoal must be taken into account when choosing the support for the preparation of iron oxide composites.